2019
DOI: 10.1039/c9ra06913e
|View full text |Cite
|
Sign up to set email alerts
|

Effects and formulation of silver nanoscaffolds on cytotoxicity dependent ion release kinetics towards enhanced excision wound healing patterns in Wistar albino rats

Abstract: A sustained and controlled release of silver ions from AgNPs is driven by greater percentage of wound contraction with minimal cytotoxic behavioural rates and effective antibacterial activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 92 publications
0
12
0
Order By: Relevance
“…After 6 and 12 days, wounds dressed in the Ce-nGel and Ce-nGel-Glu achieved a large closure of around 95%, in contrast to 65% wound closure of the bare wounds (Figure 8). Therefore, in vivo study of Sprague-Dawley rats confirmed the increased wound healing ability of the as-fabricated Ce-nGel-Glu (Ghobril & Grinstaff, 2015;Sethuram et al, 2019;Zhang et al, 2020).…”
Section: Histological Evaluationmentioning
confidence: 73%
“…After 6 and 12 days, wounds dressed in the Ce-nGel and Ce-nGel-Glu achieved a large closure of around 95%, in contrast to 65% wound closure of the bare wounds (Figure 8). Therefore, in vivo study of Sprague-Dawley rats confirmed the increased wound healing ability of the as-fabricated Ce-nGel-Glu (Ghobril & Grinstaff, 2015;Sethuram et al, 2019;Zhang et al, 2020).…”
Section: Histological Evaluationmentioning
confidence: 73%
“…The conventional bilayer non-adhesive pad was obtained through Dakar Company (medical safety private emergency limited, located in Israel) and the samples were characterized. 19 The bilayer non-adhesive pad was cut into small pieces and dissolved in purified de-ionized water/ammonia solution prior to homogenization process. Centrifugation was done for 15 minutes at 8000 rpm to prepare a transparent solution.…”
Section: Silver Bandaid -Silver Nanoparticle (Sbd-agnps)mentioning
confidence: 99%
“…PVA-AgNPs incorporated with CAM accelerates the wound healing potential in wistar albino rat models and found comparatively more effective than other synthetic polymer capped AgNPs which is reported in the previous study. 19 Eugenol is an antimicrobial phenolic component of cinnamon essential oil known for anti-inflammatory, antioxidant, anticarcinogenic and analgesic properties. 20,21 Eugenol is highly volatile and insoluble in water that gets affected by enzymatic and chemical degradation, and losses occur due to thermal decomposition and volatilization.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, ZnO is less toxic and serves as a source of Zn, that is required by 300 catalytic enzymes that influence cell differentiation and proliferation as well as wound healing 17 . Likewise, Ag NPs have gained a new therapeutic potential to be employed in wound dressings owing to their safety, reliability, low toxicity, potency, and resistance to various bacteria 18 . The unique physicochemical properties of these NPs are suitable for enhanced encapsulation, active and passive targeted delivery, and regulated and sustained drug release 19 , 20 .…”
Section: Introductionmentioning
confidence: 99%
“…The unique physicochemical properties of these NPs are suitable for enhanced encapsulation, active and passive targeted delivery, and regulated and sustained drug release 19 , 20 . Therefore, various nano-based dressinghave been fabricated by the integration of NPs with different biocompatible polymers, like chitosan, polylactic acid (PLA), polyvinyl pyrrolidone (PVP), and polyvinyl alcohol (PVA), for efficient wound healing applications 18 , 19 , 21 .…”
Section: Introductionmentioning
confidence: 99%